PROSES PEMBUATAN BATU BATA BERPORI DARI TANAH LIAT DAN KACA - Hastutiningrum, Sri (JURNAL TEKNOLOGI TECHNOSCIENTIA, 2013)
Brick is one of the ingredients of making buildings that currently needs increased mainly due to the porous bricks are stronger and lighter than ordinary bricks, making it great for the foundation of the building. Making bricks porous can use material stuffing form of foam, paper, a rice husk and organic materials. In this research are tried making bricks porous by the use of stuffing form of paper, where these materials are so easily we get. Raw materials used for the manufacture of a porous bricks is glass, clay and water. The purpose of this study was to determine the influence of glass to powerful press of porous brick. Generally, making of porous brick is mixing by powder paper, clay, glass and a little water and then made of dough. Printed and dried dough until weighs constant, then burned in muffle with temperature and time that given. Bricks which has been so then tested strong complained bitterly. The variables used are variable of ratio of clay and glass 1: 1, 1: 1,5, 1: 2, 1: 2.5, and 1: 3, variable of burning time 60 minutes, 90 minutes, 120 minutes, 150 minutes, and 180 minutes and variable of burning temperature 600 oC, 650 oC, 700 oC, 750 oC, and 800 oC. Based on the results of the research that has been done, press optimum strength obtained is 35,26 kg/cm2 with clay and glass ratio 1: 2, while the combustion time 60 minutes, gained strong press optimum of 35,26 kg/cm2 and burning temperatures 700 oC obtained strong press optimum of 36,58 kg/cm2.